(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the effect of workplace flexibility on millennial job engagement in state hospitals within Ogun West Senatorial District, Nigeria, drawing on the Job Demands–Resources (JD‑R) Model. A descriptive cross-sectional survey was conducted among healthcare professionals in two state hospitals in Ogun West, with a total population of 246 and a proportionate sample of 151 respondents selected through probability-based methods. The study employed a structured questionnaire comprising 16 items on workplace flexibility, 15 on autonomy, 14 on professional growth, and 13 on engagement, all measured on a 5-point Likert scale. A pilot study with 30 healthcare professionals was used to validate the instrument. Data were analysed using IBM SPSS Statistics (version 28.0), including descriptive statistics, Pearson correlation analysis, and multiple linear regression. The study found that workplace flexibility, autonomy, and professional growth are positively linked to engagement, with autonomy and professional growth identified as significant predictors, and the regression model explaining 42% of the variance in engagement (R² = 0.42; F(2, 148) = 24.87; p < 0.01). A small minority reported that excessive autonomy created ambiguity and stress, suggesting that autonomy should be structured by clear expectations and feedback. The findings are situated within emerging evidence on generational differences in Nigerian healthcare. The study recommends that hospital administrators and policymakers implement structured autonomy, strengthen professional development systems, and institutionalise flexible work policies to enhance millennial engagement and retention.